Factors affecting myopia control outcomes with orthokeratology treatment in children: a retrospective analysis - Wang, Fengjiao; Wang, Wenwen; Yin, Chengqiang; Yang, Shiqi; Zhan, Xiaomin; Chen, Huan; Deng, Jun (Frontiers in Medicine, 2025)
PurposeThis retrospective observational cohort study aimed to analyze the factors influencing the effectiveness of orthokeratology (OrthoK) lens treatment in controlling myopia in children.MethodsMedical records of 200 children aged 8–15 years, with spherical equivalent refraction (SE) ranging from −1.00 to −6.00 diopters (D) and binocular anisometropia less than 1.00 D, were analyzed. The data included baseline age, SE, keratometry readings (Kf and Ks), corneal eccentricity, asymmetry indices, pupil size, and corneal diameter. Multivariate linear regression analysis was used to identify factors associated with axial length (AL) changes over a 1 year period. Additional analyses explored the relationship between treatment outcomes and lens centration parameters.ResultsThe mean axial length (AL) growth after 1 year was 0.20 ± 0.16 mm. Multivariate analysis identified baseline age (β = −0.725, p < 0.001) and baseline SE (β = 1.289, p < 0.001) as significant predictors of AL change. Subgroup analyses showed that children older than 11 years with baseline SE greater than −3.00 D exhibited the most favorable treatment outcomes. Lens decentration patterns were significantly correlated with treatment efficacy (p < 0.05).ConclusionOrthokeratology treatment outcomes are significantly influenced by baseline age and refractive error. The findings suggest that patient age and the severity of initial myopia should be considered when predicting treatment outcomes. Further prospective studies are required to validate these findings and investigate the role of lens centration in treatment efficacy.